School Zoning Policy Controversy In Elementary Education - Dinda Febrianti Putri; Febriyanti Ghayatul Qushwa; Shahzadi Hina (EDUCARE: Jurnal Ilmu Pendidikan, 2024)
This study focuses on the education zoning policy implemented in Indonesia, intending to analyze its impact on equal access to education, parental perceptions, and the long-term quality of education. This policy is an essential issue because it can affect the distribution of students in schools and the quality of education services received by children in various regions. The purpose of this study is to evaluate the effectiveness of the zoning policy in improving access to education, understand parental perceptions of this policy, and analyze its long-term implications for the quality of education. The method used in this study is a qualitative approach with in-depth interviews with parents, teachers, and stakeholders in zoning schools. The data obtained were analyzed thematically to identify patterns and themes in the informants' responses. The summary of the conclusions of this study shows that the zoning policy has the potential to improve access to education. However, there are still challenges regarding the quality of teaching and facilities. Parental perceptions are generally positive, but there are concerns about the gap in quality between schools. These findings recommend increasing support for zoning schools to achieve the goal of more effective education equity.